Isolation and characterization of highly thermal stable microcrystalline cellulose derived from belulang grass (Eleusine indica) - Pratama, Agus Wedi; Mahardika, Melbi; Widiastuti, Nurul; Piluharto, Bambang; Ilyas, R.A.; Salit @ Sinon, Mohd Sapuan; Amelia, Devita; Firmanda, Afrinal (Elsevier, 2024)
The development of transforming Belulang grass (Eleusine indica) fiber into high-value-added products has not been explored. Microcrystalline cellulose (MCC) is a promising natural material that has been widely used in several sectors. This study is focused on the MCC isolation from Belulang grass fibers using alkalization, bleaching, and acid hydrolysis. The effects of these treatments on the chemical composition, surface morphology, crystallinity, and thermal stability of the fibers were evaluated using various techniques. Fourier-transform infrared (FTIR) analysis confirmed the removal of lignin and hemicellulose content through treatments like alkalization and acid hydrolysis. Scanning electron microscopy (SEM) revealed a transformation in the fiber surface from a bundled structure to individual rods with average lengths of 15.64 μm after acid hydrolysis. Acid hydrolysis significantly increased the cellulose content by 119.2 %, while simultaneously reducing hemicellulose and lignin contents by 72.6 % and 84.1 %, respectively. X-ray diffraction (XRD) analysis demonstrated a remarkable increase in crystallinity index from 51.87 % to 75.76 % following hydrolysis. Moreover, thermogravimetric analysis (TGA) confirmed the enhanced thermal stability of MCC, with a decomposition temperature reaching up to 366.53 °C. These findings suggest that MCC derived from Belulang grass has the potential to be a sustainable alternative to synthetic materials for reinforcing biocomposites.